Suicide and Types of Agriculture: A Time‐Series Analysis in Japan. Issue 1 (19th June 2019) - Kanamori, Mariko; Kondo, Naoki
Abstract : Objective: In recent years, rural areas have reported higher suicide rates than urban areas worldwide. Although agricultural activity is a key characteristic of many rural areas, rurality may also have heterogeneous qualities based on the type of agriculture pursued. However, to date, no study has examined potential linkages between suicide rate and types of agriculture. Method: In this study, we used 1983–2007 annual time‐series data of the standardized mortality ratio (SMR) of suicide and product‐specific agricultural outputs in Japanese municipalities to shed light on this phenomenon. We conducted a multilevel linear regression analysis, taking into account a hierarchical structure of the time‐series data, limiting our analysis to municipalities where agricultural land use was high. Results: Our multilevel analysis showed that the animal husbandry output was positively associated with suicide SMR in both women and men, with a stronger relationship among women, whereas no association was observed in agricultural crop output. Temporal analysis showed that the association could be observed consistently throughout the period between 1983 and 2007. Conclusions: This study raises the possibility that the industrial and cultural characteristics of communities that rely on animal husbandry may be associated with an increased risk of suicide.